ANALYSIS OF THE STAGES OF DEVELOPMENT OF FUNDAMENTAL MOTOR SKILLS: A STUDY OF STUDENTS AGED 9 AND 10 YEARS OLD (Fiep Bulletin - online, 2014)
This study's main objective is to determine the stage of development of motor skills in children aged 9 and 10 years old, male and female. Were subjected of this investigation, 30 students of the 4th year of a state school in the city of Valle Verde, RS. This study was characterized as a descriptive exploratory study and followed these steps: selection of subjects for research; observational analysis of motor skills of balance, locomotion and manipulative and their classification into stages (initial, elementary, mature). To evaluate motor abilities it was used the Instrument of Evaluating the Standard Motor Schools (FMPAI) developed by McMlenaghan and Gallahue (1982). Were observed the following balance skills: plane with the supporting foot elevated and rolling forward; locomotion skills: straight line race and jump with both feet together, and manipulative skills: launch and receive a ball, to verify the level of maturity of movement patterns. The main results were: In the motor skills of balance: rolling forward 66.7% of the subjects are in the initial stage and in the plane 43.4%  are in the elementary stage. In locomotors skills: 50% are in the elementary stage and 50% in the mature stage in the racing activity on a line and in the activity jump with both feet 45% are in elementary stage and 45% in the mature stage. In the manipulative skills, 47% are in the mature stage of the throwing the ball activity and in the receiving the ball activity, 40% are in the elementary stage. It is concluded that this study becomes effective to emphasize the importance of evaluation of motor skills in children, as it allows the teacher to identify the difficulties and needs presented by the child, and create the correct guidelines to enhance their development.
Keywords: Skills; development; school; analysis